Conformity and differentiation are two sides of the same coin. (June 2023) - Ioannou, Christos C.; Laskowski, Kate L.
Highlights: Socially driven behavioural conformity is key in social learning, cultural transmission and collective behaviour, whereas socially driven behavioural differentiation occurs in leadership, dominance hierarchies, and division of labour. While traditionally studied as separate phenomena, we propose that behavioural conformity and differentiation are two sides of the same coin, each being defined by their impact on interindividual (and group) behavioural variation. Analysing interindividual behavioural variation is already widespread across the behavioural sciences and so considering conformity and differentiation together requires only a shift in perspective, not a shift in methods. Quantifying conformity and differentiation on the same scale enables stronger tests of alternative hypotheses about the feedbacks occurring between individual behaviour and social processes. Abstract: Variation between individuals is a key component of selection and hence evolutionary change. Social interactions are important drivers of variation, potentially making behaviour more similar (i.e., conform) or divergent (i.e., differentiate) between individuals. While documented across a wide range of animals, behaviours and contexts, conformity and differentiation are typically considered separately. Here, we argue that rather than independent concepts, they can be integrated onto a single scale that considers how social interactions drive changes in interindividual variance within groups: conformity reduces variance within groups while differentiation increases it. We discuss the advantages of placing conformity and differentiation at different ends of a single scale, allowing for a deeper understanding of the relationship between social interactions and interindividual variation.